Limited Liability and Option Contracts in Models with Sequential Investments - Christoph Lülfesmann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
The paper investigates a model where two parties sequentially invest in a joint project (an asset). Investments and the project value are unverifiable, and A is wealth constrained so that an initial outlay must be financed by either agent B or an external investor C, say a bank. We show that an option contract in combination with a loan arrangement facilitates first best investments and any distribution of surplus if renegotiation is infeasible. Moreover, the optimal strike price of the option is shown to differ across financing modes. If renegotiation is admitted, the first best can still be attained unless A's bargaining position is too strong. Otherwise, B financing or C financing may become strictly preferable, and a combination of multiple lenders may be optimal.
Keywords: D23; H57; L51; 330; Option Contracts; Corporate Finance; Sequential Investments; Double Moral Hazard